Polynucleotides HPT ‐Based Dermal Filler for Skin Rejuvenation: A Prospective Clinical Investigation - Chiara Teramo; Andrea Mattioli; Carolina Prussia (Journal of Cosmetic Dermatology, 2026)
ABSTRACT Background Polynucleotides (PN)‐based dermal fillers are increasingly used for skin rejuvenation due to their biocompatibility and regenerative properties. Aims This study aimed to confirm the efficacy and safety of Plinest (Mastelli) in improving skin hydration of the face, neck, and décolleté over 4 months follow‐up. Patients/Methods Participants received three injections at 2‐week intervals (at visits V0, V1, and V2), with follow‐up at two (V3) and 4 months (V4) after last injection. The primary outcome was aesthetic improvement measured by the Global Aesthetic Improvement Scale (GAIS), while secondary outcomes included skin hydration, elasticity, turgor, patient satisfaction, and tolerability. Results Twenty‐eight subjects were enrolled. GAIS scores showed significant improvement across all areas from baseline to V4, with a median increase of 2 points, as reported by subjects and investigator. At V1, facial skin hydration increased from 48.8% ± 5.9% to 50.4% ± 6.9%, with similar trends in neck and décolleté. A slight decline was observed at V2, followed by a peak at V3 before stabilizing at V4 (face: 49.6% ± 6.2%, neck: 50.6% ± 7.3%, décolleté: 47.4% ± 4.1%). Skin elasticity improved between V0 and V4, with mean differences ranging from 5 to 11 N/m. Pain was moderate, with higher intensity in the face and neck compared to the décolleté. Despite this, participants were highly satisfied, with scores between 4 and 5 at V3 and V4. Adverse events were mild and transient. Conclusion These findings confirm the efficacy and safety of the device in improving skin hydration and demonstrate high patient satisfaction.